Illustration by Pasternak of Tolstojs novel "War and Peace". From: Bro 605/4 fol, nr.28 - Pasternak, Leonid, (1953)
Illustration by Pasternak of Tolstojs novel "War and Peace". From: Bro 605/4 fol, nr.28.